Air condition controller using mobile technologies - Tahboub, Hamdi; Abu Zaneh, Saadi (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2007)
the smart home offers a new opportunity to augment peoples lives with ubiquitous computing technology that provides increased communications , awareness and functionality . mobile technology .....
Keywords: Air condition; mobile technologies